Body Mass Index Trajectories From Childhood to Adulthood and Age at Onset of Overweight and Obesity: The Influence of Parents' Weight Status. Issue 11 (22nd July 2022) - Nielsen, Jannie; Hulman, Adam; Narayan, K M Venkat; Cunningham, Solveig A
Abstract: We investigated the influence of parents' weight status on their children's growth trajectories and its association with age at onset of overweight and obesity. We used 16, 396 height and weight records from 3, 284 youths from the Panel Study of Income Dynamics, followed across childhood into adulthood (United States, 1997–2017). Across age groups, we modeled body mass index trajectories (ages 5–32 years) according to parents' weight status, using mixed-effect models to estimate age at onset of overweight and obesity and proportion with obesity from childhood to adulthood. There were large differences in growth patterns according to parents' weight status: Children of parents with obesity had, on average, overweight at age 6 (95% confidence interval (CI): 5, 7) and steep growth trajectories until age 12; children of normal-weight parents had slower increases in body mass index, reaching overweight on average at age 25 (95% CI: 24, 27). By age 30, 30% (95% CI: 28, 31) of youths had obesity. Differences in early-life growth persisted into adulthood: 48% (95% CI: 45, 52) of adult children of parents with obesity had obesity versus 16% (95% CI: 14, 19) of those of normal-weight parents. Trajectories to unhealthy weight were heavily influenced by parents' weight status, especially before age 12, children of parents with obesity having overweight 19 earlier in life than children of normal-weight parents.